Integration of Artificial Intelligence in Mathematics Learning: An Effort to Improve Creative Thinking Abilities - Hamid, Nurqiyamah; Haidar, Irajuana; Bahar (Jurnal Pedagogi dan Inovasi Pendidikan, 2025)
The existence of artificial intelligence (AI) technology has experienced very rapid development recently. This phenomenon opens up opportunities to use AI in mathematics learning. This research aims to analyze the effect of using AI on creative mathematical thinking abilities. A total of fifth-grade elementary school students with an average age of 11 years were involved as samples for this research. They come from different classes but are still at the same school. The experimental class (n1=31) was given treatment in the form of mathematics learning assisted by AI technology and the control class (n2=31) was given conventional learning. Data on creative thinking abilities were collected through pretests and posttests in the form of validated essay questions. Data on students' creative thinking abilities was then analyzed using descriptive and inferential statistics. The results of this research indicate that using AI technology in mathematics learning can be an alternative technology to improve students' creative thinking abilities.